ANALISIS MATEMATIK KINERJA KEUANGAN SEBELUM DAN SESUDAH INITIAL PUBLIC OFFERING (IPO) PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - M Sulton Maulana Hotami; Alfi Maulani (LPPM Universitas Bina Bangsa, 2023)
The Financial performance before and after the IPO of several companies has not been stable, some have increased or decreased. This research aims to analyze the company's financial performance before and after the Initial Public Offering (IPO) on the Indonesia Stock Exchange in 2019. The population in this study were companies that conducted Initial Public Offerings (IPO) listed on the Indonesia Stock Exchange in 2019 totaling 55 company. Samples that meet the criteria in this study amounted to 5 companies using the purposive sampling method. The data analysis method used in this research is the Paired Sample t-test. The ratios used as variables in the research are Current Ratio (CR), Debt to Equity Ratio (DER), Total Assets Turnover (TATO) and Return on Assets (ROA). The results of the study using the Paired Sample t-test showed that there was no significant difference in the company's financial performance before and after the IPO based on the ratio of CR, DER, TATO and ROA